Pengaruh Tingkat Pendidikan, Pekerjaan dan Kondisi Ekonomi terhadap Perilaku Ibu dalam Pemenuhan Imunisasi Dasar di Praktik Mandiri Bidan Dewi Sesmera Tanjung Mulia - Mailinda Purwanti; Chyntia Gusdelin Nabila (Pusat Riset dan Inovasi Nasional, 2025)
Immunization is one of the essential public health efforts that are effective in providing specific immunity against Immunization-Preventable Diseases. The study used a quantitative cross-sectional approach. The study sample was 33 mothers who underwent basic immunization at the Dewi Sesmera Tanjung Mulia Independent Midwife Practice. The statistical test used was the Chi-Square test and the Crostabs test. The results of the study concluded that of the 25 mothers who behaved well in fulfilling basic immunization, there were 72.7% (24 people with high education); 3.0% (1 person) with secondary education and none with low education. Furthermore, as many as 6.1% (2 people) behaved poorly with a high level of education; 18.2% (6 people) with secondary education and 0% (no one) with low education. The results of the data analysis obtained a p value = 0.000 <0.05, meaning there was an influence of education level on maternal behavior in fulfilling basic immunization at the Dewi Sesmera Tanjung Mulia Independent Midwife Practice. Of the 25 mothers with good behavior in fulfilling basic immunizations, 75.8% (25 people) were housewives and no mothers were working. Furthermore, 9.1% (3 people) had bad behavior with the status of housewives, and 15.1% (5 people) with working status. The results of the data analysis obtained a p value = 0.000 <0.05, there was an influence of work on maternal behavior in fulfilling basic immunizations at the Dewi Sesmera Tanjung Mulia Midwife Independent Practice. Of the 25 mothers with good behavior in fulfilling basic immunizations, 45.5% (15 people) had very high economic conditions, 24.2% (8 people) had middle economic conditions, 6.1% (2 people) had middle economic conditions, and 0% (none) had low economic conditions. Furthermore, 15.1% (5 people) had bad behavior with middle economic conditions, 9.1% (3 people) had middle economic conditions, there were 0% (none) with very high economic conditions and low economic conditions. The data analysis yielded a p-value of 0.008 <0.05, indicating that economic conditions influence maternal behavior in fulfilling basic immunizations at the Dewi Sesmera Tanjung Mulia Independent Midwife Practice. This study concluded that education level, occupation, and economic conditions influence maternal behavior in fulfilling basic immunizations.